Analysis Of Positioning Online Investment Apps In Indonesia - Shaury, Sofyan; Rofi, Abdur Rahman; Hartini, Sri (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to determine Online Investment in Indonesia in terms of its attributes. Online Investment such as BIBIT, AJAIB, STOCKBIT, MOST, and IPOT. The study used a quantitative method with a sample of 162 respondents. The study used multidimensional scaling analysis with SPSS Version 27. The results of the MDS analysis are that each Online Investment has its own advantages that are not possessed by others. In addition, Dimension 1 (d1) is perceived usefulness, and Dimension 2 (d2) is trust. In the perceived reputation attribute, BIBIT is superior, the trust attribute IPOT is superior, the perceived usefulness and user interface attributes can be seen between AJAIB and STOCKBIT